Nanostructured silicon materials and methods of manufacture for use in lithium-ion based secondary batteries - Patents.com
Patent Information
- Application Number
- JP2023563270
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-15
- Filing Date
- 2022-04-14
- Publication Date
- 2025-04-21
AI Technical Summary
Existing methods for producing silicon-based anodes for lithium-ion batteries face challenges such as mechanical failure due to volume change during lithium alloying, high manufacturing costs from additional processing steps, and high electrical resistance between silicon particles and conductive carbon.
A method to produce micron-sized silicon particles with nanostructures, such as through holes or channels, and a carbon coating applied without additional processing steps, enhancing electrolyte transport and conductivity.
The method results in improved battery performance with higher capacity, faster charge and discharge rates, and reduced manufacturing costs by eliminating complex coating processes.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Detailed Description of the Invention
[0001] [Field of the Invention] The present invention relates to a method for producing silicon-based particles, the particles having a nanoporous structure.
[0002] Furthermore, the present invention relates to anodes for lithium-based batteries comprising silicon materials, and to lithium-based batteries having such anodes.
[0003] [background] Silicon is a very high-capacity lithium host material. It has 10 times the lithium ion storage capacity of graphite. Consequently, silicon is useful as an anode material in high-energy-density lithium-ion secondary batteries. However, a major obstacle to the application of silicon is the large volume change associated with the lithium-silicon alloying process. This volume change can cause mechanical damage in silicon-containing anodes, such as particle fracture or separation of silicon particles from other materials in the anode or metal electrode. To overcome such damage, both the composition of the anode and the structure of the silicon in such anodes must be well designed.
[0004] Silicon powders with particle sizes greater than about 0.5 μm are known to fracture and crack when they are converted to lithium silicon alloys under battery cycling. It is also known that nano-sized silicon structures can prevent crack formation during cycling. Consequently, nano-sized silicon powders can be cycled in a stable manner once their particle sizes are below the stability limit of about 150 nm to 200 nm. However, nano-sized silicon powders are very difficult to handle in industrial processes and expensive to produce on a large industrial scale.
[0005] An approach to overcome the difficulty of handling nano-sized silicon powder in secondary batteries is to aggregate nano-sized silicon particles into micron-sized carbon particles (scaffold particles, pomegranate particles). The drawback of such an approach is that it requires additional complex and expensive material processing steps, resulting in high-cost materials.
[0006] Another strategy for applying silicon to lithium-ion secondary batteries is to fabricate it as a micrometer-sized powder with an internal nanostructure to overcome the breakage problem. This approach can solve mechanical problems such as crack formation during lithiation and separation of the silicon from the anode matrix. In the form of micrometer-sized particles, such silicon materials are highly compatible with existing anode manufacturing processes.
[0007] Examples of such submicron structured porous silicon for lithium ion battery anodes are: US Patent Application Publication No. 2018069234 Nexeon;Electroactive materials for metal-ion batteries; U.S. Patent Application Publication No. 2015072240 (LG Chem); Porous silicon-based particles, method of preparing the same, and lithium secondary battery including the porous silicon-based particles.
[0008] These references disclose methods based on metal (Ag, Cu) assisted etching (US Patent Application Publication Nos. 2018069234 and 2015072240) applied to micron-sized silicon particles. Such processes can partially convert such silicon materials into nanostructured particles. Based on the nature of the etching process, the structured silicon particles consist of a "non-structured silicon" core, which is necessary to prevent the collapse of the etched structured portion of the silicon.
[0009] The next step in the manufacture of such silicon particle-containing anodes is the formation of a slurry, which is then coated onto a metal foil using a doctor blade or slot die coating process, or the like.
[0010] More specifically, the anode coating process involves mixing nano-sized structured silicon material with a binder material (e.g., polyacrylic acid) and conductive carbon (e.g., carbon black, carbon nanotubes, or carbon fibers) in a solvent (e.g., water). This anode coating process may also include the addition of synthetic or natural graphite powder. The material is mixed with the solvent to obtain a liquid slurry, which can be coated onto a metal electrode (e.g., copper foil). After a drying process, such coated metal foil can be formed to a specific size and combined with other components, such as a separator layer and a cathode, in a secondary battery.
[0011] These processes are well known and are described, for example, in Junying Zhang et al., "High-Columbic-Efficiency Lithium Battery Based on Silicon Particle Materials," Nanoscale research letters, Issue: 1, Volume: 10, Pages: 395-395, October 8, 2015.
[0012] While such processes result in reasonably functional anodes, the electrical resistance between the silicon particles and the conductive carbon is often high. To improve the performance of such anodes, an additional silicon surface coating step can be applied. Examples of amorphous carbon coatings produced in high temperature carbonization processes under argon are, for example: U.S. Patent No. 9,559,355, Hydro-Quebec, Particulate Anode Materials and Methods For Their Preparation is described in.
[0013] Silicon-coated anodes exhibit superior performance in terms of battery life and charging rate. The drawback is that the additional coating step, which is often at high temperature, increases the manufacturing cost of such anodes.
[0014] It is an object of the present invention to overcome or mitigate one or more of the disadvantages from the prior art.
[0015] [Summary of the Invention] This objective is achieved by a method for producing silicon-based particles as described in claim 1. The present invention discloses a silicon material consisting of micron-sized particles, each of which has a nanostructure, and a method for producing such silicon particles. In contrast to the prior art, this production method allows for fully structuring the particles, thereby overcoming the limitations of the unstructured volume within the particles and preventing collapse. The nanostructure of such particles has the form of through-holes or channels extending through the particle and connecting two surfaces of the particle. Optionally, if the channels are branched within the particle, they can connect two or more surfaces. These channels are more effective at transporting liquid electrolyte into the silicon than the prior art, which discloses holes with a single opening on one surface. The improved electrolyte transport properties combined with the fully structuring of the particles result in better battery performance, higher capacity, and improved charge and discharge rates compared to the prior art.
[0016] The manufacturing method also discloses a carbon coating that is applied to the silicon without the need for additional process steps. In the prior art, carbon coatings are applied using coating steps such as high temperature carbonization or chemical vapor deposition processes. Such additional processing steps are eliminated by the disclosed method.
[0017] Furthermore, the present invention relates to a powder of silicon-based particles as set forth in claim 13. The present invention also relates to an anode for a secondary battery and a lithium-based secondary battery. [Brief explanation of the drawings]
[0018] The present invention will be described in more detail below with reference to the drawings, in which exemplary embodiments of the invention are shown. The drawings are intended for illustrative purposes only and are not intended as a limitation on the concepts of the invention. The scope of the invention is limited only by the definitions set forth in the appended claims. [Figure 1]FIG. 1 shows the layer structure of a lithium-ion based secondary battery with different components. [Figure 2] FIG. 1 shows the composition of the anode consisting of structured silicon, conductive carbon, and a binder on a metal electrode. [Figure 3] 1 is a surface scanning electron micrograph of a cross section of an anode comprising such a structured silicon material. [Figure 4] 1 is a surface scanning electron microscope photograph of a silicon powder particle with a submicron structure. [Figure 5] 1 is a graph showing an example of particle size distribution measurement of a micron-sized nanoporous silicon particle sample having a median (D50) particle size of 7.9 μm. [Figure 6A] FIG. 1 is a schematic diagram of submicron structured silicon particles demonstrating phase change shape during the first charge of a secondary battery. [Figure 6B] FIG. 1 is a schematic diagram of submicron structured silicon particles demonstrating phase change shape during the first charge of a secondary battery. [Figure 7A] FIG. 1 is a schematic diagram of a submicron structured silicon particle in a charged state. [Figure 7B] FIG. 1 is a schematic diagram of a submicron structured silicon particle in a discharged state. [Figure 8] FIG. 1 shows the X-ray photon emission spectroscopy spectrum of such a micron-sized silicon powder at energies close to the carbon C1s peak. [Figure 9] 1 is a graph showing the charge-discharge efficiency-coulombic efficiency of a nano-sized structured silicon material anode compared to a non-structured silicon material anode.
[0019] [Detailed technical explanation] FIG. 1 shows the layer structure of a lithium-ion based secondary battery with its different components.
[0020] Lithium-ion secondary batteries are fabricated from a layered stack including an anode, a separator, and a cathode, as shown schematically in FIG. 1. 1002 is the anode of the battery 1000, which in this case primarily comprises a nano-sized structured silicon material combined with a binder material for improved mechanical stability and a conductive additive for improved electrical conductivity. 1003 is the separator layer, which is fabricated from an electrically insulating material (e.g., porous polypropylene foil or glass fiber cloth) that allows electrolyte penetration. The separator layer 1003 prevents short circuits between the anode 1002 and the cathode 1004, which could result in catastrophic failure of the secondary battery. 1004 represents the active cathode layer, which comprises a lithium-containing metal oxide or metal phosphide with a conductive additive for improved electrical conductivity and a binder for mechanical stability. The secondary battery stack is filled with a lithium-ion-containing electrolyte 1005.
[0021] During charging of the battery 1000, lithium ions are extracted from the cathode 1004 and transported and stored in the anode 1002. During discharge of the battery 1000, the anode 1002 releases the stored lithium ions, which are transported back to the cathode 1004. It is clear that the overall energy density of the battery 1000 having stacked anode and cathode layers 1004, 1002 is primarily determined by the specific lithium storage capacities of the anode and cathode materials and the chemical potentials of the anode and cathode with respect to the Li / Li+ transition. Therefore, it is preferable to use cathode and anode materials that have a high specific capacity and a large potential difference for lithium ions.
[0022] An example of an advanced anode material is silicon, which has an approximately 10-fold increased specific capacity compared to graphite. Silicon materials have a specific capacity of 3590 mAh / g Li 3.75 It can be converted into a Si alloy.
[0023] However, silicon is converted to Li 3.75The process of conversion to Si and vice versa causes large volume expansion and contraction of the silicon material during each battery cycle. The volume change induces mechanical stresses on the silicon material itself and the surrounding anode structure, resulting in rapid capacity fade of the battery.
[0024] To overcome such failure, both the silicon material and its interactions with other components of the anode must be designed to mitigate the volume expansion of the silicon material during cycling, which will have the consequence of stabilizing the anode and therefore the battery.
[0025] A first embodiment of the present invention describes a method for producing silicon materials, including an advantageous carbon surface coating on silicon and the application of this carbon surface coating in a high energy density lithium ion secondary battery system.
[0026] The method detailed below consists of three processing steps: Step 1: Rapid directionally solidifying a metal-silicon melt at or near the eutectic melt composition of the metal-silicon system into a solid two-phase material consisting of a metal silicide phase and a silicon phase; Step 2: A wet chemical etching step is used to dissolve the metal silicide phase from the solidified material, followed by Step 3: Milling the etched solidified material while contacting it with a carbon-containing material.
[0027] These three steps are described in detail below: The first step in the method for producing silicon materials involves rapid directional solidification of a liquid silicon-metal-containing melt. In one embodiment, the process is described in the form of a liquid silicon-chromium melt, although silicon combined with other metals, such as titanium or vanadium, may alternatively be used.
[0028] When a liquid melt with a composition at or near the eutectic ratio of chromium and silicon is rapidly solidified, phase separation occurs, resulting in a two-phase structure in the form of lamellar structures of chromium disilicide and silicon phases. A model that explains the structure geometry depending on the crystallization rate was published by Jackson and Hunt (Jackson KA, Hunt JD, Lamellar and rod eutectic growth [J]. Trans Met Soc AIME, 1966, 236: 1129-1142.).
[0029] The lamellar or rod-like silicide and silicon phases extend in the direction of crystallization front movement and have typical dimensions (defined as the distance between the chromium disilicide phase and the continuous silicon phase) that depend on the crystallization rate. Therefore, a well-controlled crystallization process that allows for a nearly constant crystallization rate can be used as a method to produce such uniformly spaced chromium silicon disilicide materials.
[0030] A preferred crystallization process for this method is described, for example, in German Patent Application Publication No. 3419137 for semiconductor foils, in which an undercooled substrate is transported under a casting frame filled with a eutectic composition melt. The crystallization process begins when the undercooled substrate contacts the melt in the casting frame and continues throughout the substrate's transport time in contact with the melt. Because the crystallization direction is perpendicular to the plane of the substrate surface, the lamellar or rod-like structures are also oriented perpendicular to the substrate surface. This process allows for high and well-controlled crystal growth rates, so that the eutectic chromium-silicon melt crystallizes with a well-defined, oriented eutectic two-phase structure. The controllable crystallization rate of the casting process combined with the chromium-silicon eutectic melt results in a structured two-phase material whose structure dimensions (i.e., the characteristic distance between a pair of parallel silicon thin layers) can be adjusted in a technically relevant range between 100 nm and 1500 nm by varying the thermal contact with the substrate and the temperature difference between the substrate and the melt.
[0031] The second step of this method involves selective etching (and removal) of the metal silicide. Most metal silicides can be etched with a dilute hydrogen fluoride solution. Because hydrogen fluoride does not react with silicon, a selective etching process is established. As a result of such a process, a sheet of material is obtained in which the metal silicide phase has been removed and a nanoporous silicon structure has been obtained.
[0032] The etching process can be carried out at room temperature, although a relatively high temperature can be useful to increase chemical reactivity. The concentration of the hydrogen fluoride solution can be adjusted to improve the process yield, shorten the processing time, and optimize the use of the etchant in the process. It is also known that most of the reaction components can be recycled in the form of metal oxides, silicon oxide, and hydrogen fluoride. As a result, the etching process is very well suited to producing nanoporous structured silicon materials in a cyclic process with minimal waste of by-products.
[0033] As a final step in the etching process, the etched silicon material is removed from the etchant and rinsed with water.
[0034] The final step involves milling the etched nanostructured silicon material to obtain micron-sized silicon powder. Ball milling or drum milling are methods that can be applied to this process depending on the intended production volume, although for larger scale production a continuous milling process with selective particle size filtering, such as jet milling, may be preferred.
[0035] While milling produces micron-sized silicon powder material with desirable nanostructured porosity, milling does not result in optimal electrical conductivity when the milled silicon material is included in an anode coating.
[0036] FIG. 4 shows a surface scanning electron micrograph of a submicron-structured silicon powder particle of a micron-sized silicon powder. Typical average particle sizes are between 1 μm and 20 μm. The nano-sized structure of the particle shows oriented channels extending through the particle and connecting two surfaces of the particle, with typical channel dimensions in this example between 100 nm and 500 nm. The channel orientation can be seen in the form of holes in surface 4001 or channels in surface 4002, depending on the orientation of the particle in the photograph.
[0037] Figure 5 shows an example of the particle size distribution of such a micron-sized silicon powder. In this example, the average particle size (D50) is 7.9 μm, while D10 = 2.7 μm and D90 = 17.5 μm. It is understood that the particle size distribution can be adjusted during the milling process. For practical reasons in the battery manufacturing process, the average particle size is preferably between 1 μm and 20 μm.
[0038] According to an embodiment of the present invention, the milling of the silicon material is carried out while in contact with a carbon-containing material, which may include, but is not limited to, at least one of carbon black, graphite, hard carbon, carbon nanotubes, graphene, acetylene black, and carbon fiber.
[0039] In the milling process, silicon sheet material is continuously broken, creating silicon surfaces with reactive dangling bonds. The dangling bonds can react with carbon-containing materials or carbon-containing milling equipment components involved in the milling process to form silicon carbide bonds with carbon-containing aggregates or particles. Thus, carbon-containing aggregates or particles are composed of carbon-containing materials chemically bonded to the surface of silicon particles. In some cases, carbon-containing aggregates or particles form a coating layer that partially or completely covers the outer surface of silicon particles.
[0040] As an example, the addition of 1 wt % to 10 wt % carbon black during the milling step has been shown to improve the conductivity between the silicon particles and the anode structure, and increase the cycle life of batteries produced with such anodes.
[0041] It is preferred to carry out the milling step in a dry milling process to allow contact between the dangling bonds in the freshly broken silicon and the carbon-containing material, whereas in a wet milling process the dangling bonds on the silicon surface are more likely to react with the moist environment, whereas in a dry milling process chemical bonding to the conductive carbon particles is more likely to occur.
[0042] Another improvement is to carry out the milling step under a protective gas atmosphere, for example under a gas such as argon, which prevents the competitive reaction of the dangling silicon bonds with atmospheric oxygen.
[0043] 8 shows an X-ray photon emission spectroscopy spectrum at energies near the carbon C1s peak 7001 of a submicron structured silicon powder produced according to the present invention and milled in contact with carbon black powder. The higher energy section in the spectrum 7002 indicates the presence of C-O bonds, and the lower energy section 7003 indicates the presence of Si-C bonds. In this example, the carbon black particles are chemically bonded to the silicon surface in the form of a carbon coating.
[0044] The combination of milling the silicon material and exposing it to a carbon material results in a nanostructured, micron-sized, carbon-coated silicon material that, when combined with other components of a lithium-ion secondary battery anode, exhibits improved performance. The greatly improved conductivity of the anode silicon material enhances anode performance, while the silicon nanostructure allows for stable electrical cycling and prevents crack formation or anode delamination, as demonstrated in the application examples below.
[0045] In another embodiment, the order of the etching and milling steps is reversed. First, a milling step can be performed on the solidified two-phase material to produce a powder consisting of particles with a metal silicide-silicon two-phase structure. Carbon-silicon bonding can be achieved in a similar manner as described in the previous embodiment. After the milling step, the powder is selectively etched using a process similar to that described above. This etching dissolves the metal silicide phase, producing a nanoporous silicon material according to the present invention.
[0046] According to one embodiment, an additional mechanical crushing step is added after the solidification step to produce metal silicide-silicon pieces from the solidified material cast, which may be advantageous to provide material pieces that can be more efficiently handled in subsequent chemical processing.
[0047] According to one embodiment, the reaction with carbon-containing material during the milling step can be omitted to produce nanostructured silicon particles.In this case, the nanostructured silicon particles typically form a natural silicon oxide surface.Nanostructured silicon particles with a natural silicon oxide surface can be useful, for example, in combination with coating processes based on the presence of a silicon oxide surface that reacts with organic molecules.
[0048] [Example] (Figure 3) An example of an anode containing such a silicon material is shown in Figure 3. Shown is a surface scanning electron microscope cross-section of an anode comprising structured silicon material 3002, carbon black 3003, and a binder on a copper foil 3001.
[0049] The anode composition in this example contains 80 wt% nanoporous structured silicon milled in contact with 5 wt% carbon black. 5 wt% graphite powder was added during slurry preparation in polyacrylic acid solution. The final anode composition consists of 80 wt% silicon, 5 wt% carbon black, 5 wt% graphite, and 10 wt% polyacrylic acid.
[0050] When a silicon-containing anode of this composition is combined with, for example, a lithium nickel manganese cobalt oxide cathode (NMC), it is preferable to match the capacities of the anode and cathode so that the silicon-containing anode charges to a specific capacity between 1000 mAh / g and 2000 mAh / g, well below the maximum capacity of silicon of 3590 mAh / g.
[0051] Therefore, such a match would place the silicon-containing anode in this example at 3 mAh / cm 2 The areal loading of silicon would be, for example, 1.5 mg / cm. 2 or 3 mg / cm 2 When adjusted to 2000 mAh / g (1.5 mg / cm), the silicon material has a 2 load) or 1000mAh / g (3mg / cm 2 This application of silicon-containing anodes has significant advantages in terms of cycle life and stable battery performance.
[0052] When silicon is alloyed with lithium, it is observed that the silicon undergoes two phase changes: crystalline Li 3.75 Before being converted to Si, amorphous Li 3.4 It is converted into the Si phase. Lithiation is 3.4 When the silicon content is limited to well below the Li-Si ratio (approximately 3200 mAh / g), some of the silicon material is converted to Li 3.4 A two-phase material exists in which a portion of the silicon has been converted to Si, while another portion of the silicon remains in its crystalline state.
[0053] The advantage of this use of silicon (i.e., capacity-limited loading (limited lithiation as described above)) is that the remaining crystalline silicon phase mechanically stabilizes the silicon particles and forces the expansion of the silicon into the internal porosity of the particles. This effect significantly reduces the mechanical load on the anode composition and improves the cycling stability of the battery. This effect also prevents external expansion of silicon anode-containing batteries, which is one of the major obstacles in applying silicon-dominated anodes.
[0054] The effect of capacity-limiting loads is explained in more detail with reference to Figures 6A, 6B and 7A, 7B. Figures 6A, 6B show a schematic diagram of a submicron structured silicon particle during a first charge. The initial silicon particle 5000 (Figure 6A) consists of a pure crystalline silicon phase 5001. During the first charge cycle, the crystalline silicon is dissolved in amorphous Li 3.4 During the first charge, crystalline silicon (silicon phase) 5001 and amorphous Li 3.4 Both the LiSi phase 5002 and the LiSi phase 5003 coexist together (Figure 6B). Depending on the amount of lithiation, the material can be divided into amorphous LiSi phases and amorphous LiSi phases. 3.4 At even higher lithiations, the composition Li 3.75 A silicon alloy with Si is formed. 3.4 For capacity-limited cycling well below the capacity for complete conversion to the Si phase, the two phases of the material continue to coexist.
[0055] 7A and 7B show schematic diagrams of submicron structured silicon particles 6000 during successive charging (FIG. 7A) and discharging (FIG. 7B) conditions under capacity-limited battery cycling. The lithium-containing (charged) silicon particles are composed of crystalline silicon 6001 and amorphous Li 3.4 After discharge, amorphous Li 3.4 The Si phase is converted to amorphous silicon 6003. During successive battery cycling at the same or lower capacity, the amorphous silicon-Li 3.4 Only the Si volume is activated: the remaining crystalline silicon 6001 is not significantly altered and mechanically stabilizes the (porous) particles.
[0056] Figure 9 shows the charge-discharge efficiency-coulombic efficiency of silicon material anodes. Reference numeral 8001 shows the coulombic efficiency versus cycles for two samples containing nanostructured silicon material according to the present invention. Reference numeral 8002 shows the coulombic efficiency versus cycles evolution for micron-sized unstructured silicon. Both materials had the same particle size distribution and anode composition. Anodes were prepared using 80 wt% silicon with 10 wt% conductive carbon and 10 wt% polyacrylic acid as a binder. Cycling was performed against a lithium metal disk with a capacity limit of 1000 mAh / g silicon. A test cycle with a 2-hour charge time and a 2-hour discharge time was used for all samples.
[0057] This example demonstrates the application of nanostructured, micron-sized, carbon-coated particles produced by a method according to one embodiment of the present invention.
[0058] The present invention has been described with reference to preferred embodiments. Obvious modifications and alterations will occur to others upon reading and understanding the preceding detailed description. It is intended that the invention be construed as including all such modifications and alterations insofar as they fall within the scope of the appended claims.
Claims
1. 1. A method for producing silicon-based particles, comprising: preparing a eutectic metal silicon melt from constituent metal and silicon; contacting the eutectic metal silicon melt with a supercooled substrate while controlling the time the substrate is in contact with the melt to produce a solidified eutectic metal silicon plate or flake consisting of a metal silicide phase and a silicon phase by a controlled directional solidification process of the eutectic metal silicon melt, forming a lamellar or rod-like eutectic cast structure of the silicon phase lamellae or rods and the metal silicide phase lamellae or rods parallel to each other in a direction perpendicular to the substrate; producing nanostructured, micron-sized silicon-based particles by exposing the solidified eutectic metal silicide silicon plates or flakes to milling and etching steps; The etching step includes exposing to a selective chemical etching process configured to dissolve the thin layers or rods of the metal silicide phase in the directionally solidified thin layered or rod shaped eutectic cast structure and to form parallel oriented channels in the silicon phase at the locations of the dissolved thin layers or rods of the metal silicide phase, thereby the silicon-based particles are each configured to have a channel at the location of each dissolved layer or rod of the metal silicide phase that penetrates completely through the silicon-based particle and connects at least two surfaces of the silicon-based particle.
2. The method of claim 1 , wherein said silicon-based particles have a plurality of channels oriented parallel to one another between said at least two surfaces.
3. The method of claim 1 or 2, wherein the step of crushing the solidified eutectic metal silicide silicon plates or flakes is performed after the etching step.
4. The method of claim 1 or 2, wherein the step of crushing the solidified eutectic metal silicide silicon plates or flakes is performed before the etching step.
5. 3. The method according to claim 1 or 2, wherein the grinding process is selected from the group comprising ball milling, drum milling, jet milling.
6. When the grinding step is performed after the etching step, 4. The method of claim 3, further comprising the step of forming chemical bonds of carbon-based aggregates on the outer surface of the silicon-based particles by adding a carbon-containing material comprising at least one selected from the group comprising carbon black, graphite, hard carbon, carbon nanotubes, graphene, acetylene black, and carbon fiber during the grinding process.
7. The method of claim 6 comprising creating carbon-based aggregates or particles on an exterior surface of the silicon-based particles.
8. The method of claim 7 comprising creating a silicon carbide layer disposed between the outer surface of the silicon-based particle and the carbon-based aggregate or carbon-based particle.
9. 3. The method of claim 1 or 2, wherein the metal of the metal silicon melt is chromium and the crystallization rate of the eutectic metal silicide silicon structure during the controlled directional solidification is 0.1 mm / sec or greater.
10. The method of claim 7, wherein the metal of the metal silicon melt is chromium and the crystallization rate of the eutectic metal silicide silicon structure during the controlled directional solidification is 0.1 mm / sec or greater.
11. The method of claim 1 or 2, wherein the parallel oriented channels of the silicon-based particles have a diameter between 100 nm and 1000 nm.
12. The method according to claim 1 or 2, wherein the wall between two parallel oriented channels of the silicon-based particle has a minimum thickness of between 100 nm and 1000 nm.
13. The method of claim 11, wherein the wall between the two parallel oriented channels of the silicon-based particle has a minimum thickness of between 100 nm and 1000 nm.
14. 3. A method for making an anode for a secondary battery from at least a nanostructured, micron-sized powder of silicon-based particles produced by the method of claim 1 or 2.
15. A powder of silicon-based particles produced by the method according to claim 1 or 2.
16. 16. The powder of claim 15, wherein said silicon-based particles are micron-sized and each have a nanoporous structure including at least one channel that penetrates completely through said silicon-based particle and connects at least two surfaces of said silicon-based particle.
17. 16. The powder of claim 15, wherein said silicon-based particles are micron-sized and each have a nanoporous structure comprising a plurality of channels oriented parallel to one another completely through said silicon-based particle and between at least two surfaces of said silicon-based particle.
18. 18. The powder of claim 17, wherein the parallel oriented channels have a diameter between 100 nm and 1000 nm.
19. 18. The powder of claim 17, wherein the walls between the parallel oriented channels have a minimum thickness of between 100 nm and 1000 nm.
20. 16. The powder of claim 15, wherein the carbon-based aggregates or particles are present on the outer surface of the silicon-based particles.
21. 21. The powder of claim 20, wherein the silicon-based particles include a silicon carbide layer disposed between the outer surface of the silicon-based particle and the carbon-based aggregate or carbon-based particle.
22. 3. An anode for a secondary battery comprising a silicon-based material consisting of at least silicon-based particles, the silicon-based particles being micron-sized and having a nanoporous structure comprising parallel-oriented channels that penetrate completely through the silicon-based particles and connect two opposing surfaces of the particles, the silicon-based particles being manufactured according to claim 1 or 2.
23. 23. A lithium-based secondary battery having the anode of claim 22 in combination with a cathode layer, wherein when the anode is charged to its maximum capacity, the silicon-based particles are converted to amorphous Li. 3.4 The amorphous Li is only partially alloyed with the Si phase, and the remainder of each silicon-based particle is 3.4 A lithium-based secondary battery, wherein the capacity of said cathode is selected to consist of a crystalline silicon phase adjacent to a Si phase.
24. The amorphous Li 3.4 A Si phase is formed as a layer on the walls of the parallel oriented channels of the silicon-based particles, and the formed amorphous Li 3.4 24. The lithium-based secondary battery of claim 23, wherein a Si phase is encapsulated in the silicon-based particles by the crystalline silicon phase.
25. 24. The lithium-based secondary battery of claim 23, wherein the capacity of the cathode is selected such that the anode is charged to a capacity of less than 2500 mAh / g silicon.
26. The lithium-based secondary battery of claim 24, wherein the capacity of the cathode is selected so that the anode is charged to a capacity of less than 2500 mAh / g silicon.